Image Segmentation Techniques: A Survey - Bhagwat, Manisha; Pise, Vivek (International Journal of Computer Sciences and Engineering, 2025)
The process of image segmentation is defined as the technique via which a given image is segmented into several objects, in order to further analyze objects present in the image [9]. The popularity of image segmentation is because of its importance in the area of image processing. The prime task of the researchers working in the field is to develop a method for efficient and better image segmentation. There are certain factors that affect the process of image segmentation like the intensity of image to be segmented, color, type and the noise present in the image [12]. No algorithm has been developed till date that could keep a look at all the above listed factors and then segment the image effectively so that all the problems that can come in the way of image segmentation can be avoided. This paper presents a review of some of the techniques developed for image segmentation.